Efektivitas Modul Modifikasi Penyusunan Strategi Komunikasi Perubahan Perilaku Terhadap Perilaku Tim Konvergensi Stunting Di Kabupaten Kampar Tahun 2022 - Herman S; Asriwati Asriwati; Miskah Afriany (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
The importance of behavior change communication, as shown in Pillar 2 (two) of the National Behavior Change Strategy, has been mentioned in many Government policies. Pillar 2 aims to increase public knowledge and awareness so as to trigger the implementation of positive behaviors to prevent stunting in the 1000 HPK period. The stunting convergence team of Kampar Regency has not succeeded in documenting the KPP strategy, one of which is because the KPP has not been understood so well that it is considered not to have discussed priorities. One alternative to increase capacity is to provide a modification module for the KPP strategy, it is necessary to conduct a study aimed at whether the provision of a modified module for the formulation of the KPP strategy is effective in improving the behavior of the stunting convergence team. The treatment hypothesis in this study is that the provision of a modification module for the formulation of the KPP strategy is effective in increasing the behavior of the stunting convergence team. This type of research is a Quasi Experimental Nonequivalent Control Group Design with a sample of 30 respondents (15 treatments and 15 controls) members of the stunting convergence team. Data collection techniques with pre and post. Data analysis was carried out by normality test, homogeneity test, independent t test and Normalize Gene test (N-Gain score) if there was a significant difference in the posttest value of the treatment with the control group, data presentation, and drawing conclusions. From the results of the study, the authors conclude that: there is a significant difference in the data before and after the level of knowledge from 13 respondents (43.3%) to the category of high knowledge 10 (33.3%), negative attitude changes are 14 respondents (46). ,7%) to the category of positive attitude which is 12 (40%) and the category of negative behavior is 13 (43.3%) to the category of positive attitude which is 10 (33.3%). The provision of a modified module for the formulation of an effective KPP strategy in increasing the knowledge of the stunting convergence team with the value of Sig. 0.045 and OR 0.022, presenting a modification module for the formulation of an effective KPP strategy in changing the attitude of the stunting convergence team with a Sig value. 0.022 and OR 0.063, presenting a modified module for KPP strategy formulation that is not effective in changing the behavior/actions of the stunting convergence team with a Sig value. 0.135 and OR 3.250. Modification module for the preparation of the KPP strategy can be an alternative in increasing knowledge, attitudes, but it is necessary to provide regular assistance and measurement to respondents so that changes in behavior can be seen more clearly. The limitations of the study in terms of time due to changes in behavior required measurements, longer observations and a larger number of samples to be able to see optimal results.